2013
DOI: 10.1039/c3ra43656j
|View full text |Cite
|
Sign up to set email alerts
|

α-Pyrones from the marine-derived actinomycete Nocardiopsis dassonvillei subsp. dassonvillei XG-8-1

Abstract: Seven new a-pyrones, nocapyrones H-N (1-7) were isolated from the marine-derived actinomycete strain, Nocardiopsis dassonvillei subsp. dassonvillei XG-8-1. The new structures 1-7 were determined by spectroscopic analysis, CD spectra, ECD quantum chemical calculations and the modified Mosher's method. Compounds 1, 2 and 6 showed inhibitory effects on quorum sensing (QS) controlled gene expression in Chromobacterium violaceum CV026 and Pseudomonas aeruginosa QSIS-lasI biosensors at a concentration of 100 mg mL À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…During PA14 infection of C. elegans , the pathogens produce virulence-related membrane vesicles, leading to the accretion of biofilm-like material on host intestinal cells (Irazoqui et al, 2010 ). There have been several reports on natural product-based small molecules from marine organisms, including actinomycetes showing potency against virulence of PA14 (Hentzer et al, 2003 ; Fu et al, 2013 ; Naik et al, 2013 ; Yaniv et al, 2017 ). Our results showed that Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During PA14 infection of C. elegans , the pathogens produce virulence-related membrane vesicles, leading to the accretion of biofilm-like material on host intestinal cells (Irazoqui et al, 2010 ). There have been several reports on natural product-based small molecules from marine organisms, including actinomycetes showing potency against virulence of PA14 (Hentzer et al, 2003 ; Fu et al, 2013 ; Naik et al, 2013 ; Yaniv et al, 2017 ). Our results showed that Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…As result, a promising number of novel secondary metabolites with biological properties are constantly being reported from marine actinomycetes (Feling et al, 2003 ; Lam, 2006 ; Solanki et al, 2008 ; Kang et al, 2015 ). Compounds originating from marine microbes that attenuate virulence through inhibition of quorum sensing system without bacteriocidal activities have also been reported (Fu et al, 2013 ; Naik et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…"Nocapyrone I" 43 and "M" 46 displayed inhibition of quorum sensing (QS) controlled gene expression in Chromobacterium violaceum CV026 and Pseudomonas aeruginosa QSIS-lasI biosensors. 106 Very clearly the naming of these metabolites needs revision. Saline culture of Nocardiopsis sp.…”
Section: Marine-sourced Bacteria (Excluding From Mangroves)mentioning
confidence: 99%
“…Three novel α-pyrones; nocapyrone H (1) , nocapyrone I (2) , and nocapyrone M (3) (Tables 1, 3), were extracted from Nocardiopsis dassonvillei subsp. dassonvillei XG-8-1 inhibited QS controlled virulence in P. aeruginosa QSIS-lasI biosensor and Chromobacterium violaceum CV026 at a concentration of 100 μg/mL (Fu et al, 2013). At 200 μg/ml concentration, the crude extract of Nocardiopsis sp.…”
Section: Family: Nocardiopsaceae; Genus: Nocardiopsismentioning
confidence: 99%